2019
DOI: 10.1007/s00217-019-03248-6
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean jellyfish as novel food: effects of thermal processing on antioxidant, phenolic, and protein contents

Abstract: Fishery, market and consumption of edible jellyfish are currently limited in western countries by the lack of market demand for jellyfish products and the absence of processing technologies adequate to the western market safety standards. The development of technology-driven processing protocols may be key to comply with rigorous food safety rules, overcome the lack of tradition and revert the neophobic perception of jellyfish as food. We show thermal treatment (100 °C, 10 min) can be used as a first stabiliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(77 citation statements)
references
References 56 publications
5
72
0
Order By: Relevance
“…Microalgae, seaweed and jellyfish have been studied and screened for potential product development in terms of the reuse of their biomass as fertilizers or biostimulants, or feed and food (Bleve et al, 2019;Leone et al, 2019;Torres et al, 2019). Seaweeds have already been used in the food processing industry (e.g., for production of agar, alginates), but many other applications are possible.…”
Section: Reusementioning
confidence: 99%
See 1 more Smart Citation
“…Microalgae, seaweed and jellyfish have been studied and screened for potential product development in terms of the reuse of their biomass as fertilizers or biostimulants, or feed and food (Bleve et al, 2019;Leone et al, 2019;Torres et al, 2019). Seaweeds have already been used in the food processing industry (e.g., for production of agar, alginates), but many other applications are possible.…”
Section: Reusementioning
confidence: 99%
“…As well as marine flora, marine animals that are invasive or create problems might be reused as a source for industrial processing. Jellyfish biomass has been recently recognized as a novel food source from the Mediterranean Sea (Bleve et al, 2019;Leone et al, 2019), particularly as it has been known as a delicacy in eastern Asia for hundreds of years. Even though the jellyfish body is composed of 95% water, the remaining biomass is rich in proteins and bioactive compounds.…”
Section: Reusementioning
confidence: 99%
“…Jellyfish as food is not familiar to most of western consumers, and it is negatively perceived. Therefore, new opportunities for expanding jellyfish food uses in western countries will rely on the development of new processing technologies and of market demand, which in turn will depend on increased knowledge of jellyfish as raw food material and on public perception of it [22].…”
Section: Introductionmentioning
confidence: 99%
“…Jellyfish are marketed in the form of products in brine, chilled, frozen, live, or desalted products directly ready for consumption (ready to eat). The technique of processing jellyfish is essentially based on a multi-phase drying process, using mixtures of salt and alum, and jellyfish products are typically consumed after desalting and rehydration in salads or after cooking [22].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, an increased frequency and abundance of JF outbreaks has been reported in the Mediterranean and North Sea [6], affecting fishing and sea wildlife with evident economic impacts [7,8,9]. Meanwhile, recent research studies have reported that some JF species with outbreak-forming populations in the Mediterranean Sea have biochemical and textural features similar to edible Asiatic species [10,11,12]. These native JF species in the Mediterranean Sea seem to be good candidates as a new “local seafood product” characterized by nutraceutical features [10,13].…”
Section: Introductionmentioning
confidence: 99%